Estrategias de ventas del comercio informal en el Cantón Jujan. - Mariscal Palma, Betzaida Polethe (2022)
The investigation carried out entitled "Sales Strategies of Informal Trade in the Jujan Canton", is presented as an important phenomenon today and it is gaining more and more place in the economy of Latin American countries and our country is no exception, the increase in the dynamism of informality is a structural socioeconomic setback in the Ecuadorian economy and those who develop it are considered vulnerable groups. This activity of selling and buying by natural persons without the constitution of a company or business, in most cases is due to unemployment or academic studies, these people perceive situations of demand that lead to the increase of this type of commerce, being the reason that there are no other options for sole proprietors who only want to satisfy their needs and improve their quality of life with work.